Combining AHP and TOPSIS method for logistics hub selection - Apichat Sopadang (2018)
© 2016 Inderscience Enterprises Ltd. The purpose of this paper is to propose a methodology to help identify country-level logistics hub (Thailand, Lao PDR and Vietnam) along the East-West Economic Corridor (EWEC) using two mathematical methods. Phase 1 identified five main factors impacting logistics hub selection that are derived from the literature studies. These factors are trade volume, infrastructure, institutional framework, service providers, shippers and consignees. Phase 2 utilises the analytic hierarchy process (AHP) method to define weight for each criterion. Experts in related fields were interviewed in order to make dyadic comparisons. Phase 3 focussed on the technique for order preference by similarity to ideal solution method to rate alternatives by assigning weights defined through AHP and by calculating which alternative is the nearest to the ideal solution. The findings conclude that Thailand, particularly thanks to its large trade volume, is the best country to be considered as a logistics hub for the EWEC.